Heat-insulating fire-resistant elastic ceramic aerogel and preparation method thereof

The heat-insulated and refractory elastic ceramic aerogel prepared by centripetal frozen casting and chemical vapor deposition methods solves the problems of prone to cracking and strength reduction in traditional ceramic aerogels, and achieves both high-temperature heat-insulating and refractory and elastic properties.

CN119841660APending Publication Date: 2025-04-18SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311340177.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Traditional ceramic aerogels are prone to rupture due to the discontinuous particle skeleton and the powder shedding and structural damage problems after being reinforced by one-dimensional fibers, making it difficult to achieve both high-temperature heat insulation and refractory performance.

Method used

Graphene aerogels were prepared by centripetal frozen casting technology, and ceramic components were deposited on their surface using chemical vapor deposition method, followed by heat treatment and thermal etching and oxidation, and the graphene components were removed to obtain a heat-insulating and refractory ceramic aerogel with a negative Poisson ratio effect.

Benefits of technology

The high elasticity and heat insulation and fire resistance of ceramic aerogels are achieved, and the volume shrinkage and strength reduction of traditional ceramic aerogels are avoided, and they have excellent mechanical properties and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841660A_ABST
    Figure CN119841660A_ABST
Patent Text Reader

Abstract

The invention relates to a heat-insulating fire-resistant elastic ceramic aerogel and a preparation method thereof. The preparation method of the heat-insulating fire-resistant elastic ceramic aerogel comprises the following steps: (1) filling a graphene dispersion liquid into a mold, then carrying out directional freezing casting, and after the directional freezing casting is finished, carrying out freeze drying to obtain graphene oxide aerogel; then, carrying out thermal reduction treatment to obtain elastic graphene aerogel; (2) by taking the elastic graphene aerogel as a template, performing in-situ deposition of a ceramic component on the surface of the elastic graphene aerogel through a chemical vapor deposition process, and after deposition is completed, performing heat treatment to crystallize the ceramic component to obtain graphene / ceramic composite aerogel; and (3) removing the graphene component from the graphene / ceramic composite aerogel through thermal etching oxidation to obtain the heat-insulating fire-resistant elastic ceramic aerogel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of thermal insulation ceramic aerogels, and in particular relates to a thermal insulation refractory elastic ceramic aerogel and a preparation method thereof. Background Art

[0002] Ceramic aerogel is widely used in aerospace, environmental management, industrial filtration, catalyst support and other fields due to its extremely low bulk density, excellent anti-ablation performance and extremely high specific surface area. It is a relatively promising high-temperature thermal insulation refractory material. However, traditional ceramic aerogels are very easy to break due to their discontinuous pearl necklace-like particle skeleton, which seriously limits their practical application. Researchers have tried to use one-dimensional (1D) fibers to reinforce granular aerogels. Although the material strength has been improved to a certain extent, the problems of powder shedding and structural damage caused by the weak interface interaction between the fibers and the particles cannot be avoided.

[0003] For aerogels composed of two-dimensional nanosheets, the face-to-face stacking of two-dimensional (2D) sheets also separates the aerogels into almost isolated units, thereby effectively reducing air conduction and convection. Porous ceramic structures synthesized by direct chemical reactions and template-assisted methods have gradually attracted attention. However, the ceramic aerogels prepared in this way still have problems such as volume shrinkage and strength loss. Therefore, it is particularly important to provide a method for preparing thermally insulating and flame-retardant elastic ceramic aerogels. Summary of the invention

[0004] In view of the above technical problems, the object of the present invention is to provide a thermally insulating, refractory, elastic ceramic aerogel and a preparation method thereof.

[0005] In a first aspect, the present invention provides a method for preparing a heat-insulating, refractory, elastic ceramic aerogel, the preparation method comprising the following steps: (1) placing a graphene dispersion into a mold, and then performing directional freeze casting, and then freeze drying after the directional freeze casting to obtain graphene oxide aerogel; then, performing thermal reduction treatment to obtain elastic graphene aerogel; (2) using the elastic graphene aerogel as a template, in-situ depositing a ceramic component on the surface of the elastic graphene aerogel by a chemical vapor deposition process, and performing a heat treatment after the deposition is completed to crystallize the ceramic component to obtain a graphene / ceramic composite aerogel; (3) removing the graphene component from the graphene / ceramic composite aerogel by thermal etching and oxidation to obtain a heat-insulating, fire-resistant, elastic ceramic aerogel.

[0006] Preferably, the concentration of the graphene dispersion is 2 to 14 mg / mL, preferably 4 to 12 mg / mL.

[0007] Preferably, the mold is a cylindrical hollow mold; the inner diameter of the cylindrical hollow mold is 6 to 20 mm, the height is 6 to 20 mm, and the mold wall thickness is 0.5 to 2 mm.

[0008] Preferably, the directional freeze casting is carried out in liquid nitrogen, the ambient temperature is -20 to -196°C, and the freeze casting time is 1 to 20 minutes.

[0009] Preferably, the thermal reduction treatment adopts an argon atmosphere or a nitrogen atmosphere, the thermal reduction temperature is 800-1100°C, the heating rate is 2-10°C / min, and the thermal reduction holding time is 2-4h; preferably, heating to 1000°C at a rate of 5°C / min in a nitrogen atmosphere and then keeping warm for 2h.

[0010] Preferably, the ceramic component deposited by chemical vapor deposition is boron nitride, silicon carbide, silicon nitride ceramic, preferably boron nitride ceramic.

[0011] Preferably, the deposition temperature of the chemical vapor deposition ceramic component is 500-1100° C., preferably 700-1100° C.; the deposition time is 20-120 min, preferably 20-80 min.

[0012] Preferably, the heat treatment temperature is controlled to be 1300°C < ≤ 2400°C, preferably 2000°C; the heat treatment atmosphere is argon or nitrogen atmosphere; and the heat treatment time is 1 to 3 hours.

[0013] Preferably, the thermal etching oxidation is performed in an air atmosphere, the thermal etching temperature is 600-800° C., preferably 700-750° C., and the time is 20-40 min.

[0014] In a second aspect, the present invention provides a thermally insulating, refractory, elastic ceramic aerogel obtained according to the above preparation method.

[0015] Beneficial Effects The present invention provides a method for preparing a heat-insulating, fire-resistant and elastic ceramic aerogel having a negative Poisson's ratio effect by using a sacrificial template method. First, a centripetal freeze casting technique is used to realize the construction of a three-dimensional concave structure graphene aerogel. Thereafter, the graphene aerogel is used as a template to deposit ceramic components such as boron nitride (BN) by using a chemical vapor deposition (CVI) technique. Thereafter, the graphene component is removed by oxidation thermal etching to obtain a ceramic aerogel having the same concave structure. The aerogel has a negative Poisson's ratio effect and achieves high elasticity based on the negative Poisson's ratio effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a scanning electron microscope image of the longitudinal section of the boron nitride aerogel prepared in Example 1; wherein the left image is a centripetal orientation characteristic image, and the right image is a hollow double-layer structure; Figure 2The stress-strain curve of the boron nitride aerogel prepared in Example 1 after 100 compression cycles at a compression strain of 50%; Figure 3 This is a diagram of the negative Poisson's ratio effect of the boron nitride aerogel prepared in Example 1; Figure 4 This is a flame retardant and fire resistant performance diagram of the boron nitride aerogel prepared in Example 1; Figure 5 The stress-strain curve of the boron nitride aerogel prepared in Comparative Example 1 after 10 compression cycles at a compression strain of 50%. DETAILED DESCRIPTION

[0017] The present invention is further described by way of embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, rather than to limit the present invention.

[0018] In the present invention, graphene oxide is used as a raw material, liquid nitrogen is used as a cold source, and a graphene aerogel is obtained by centripetal freeze drying technology, freeze drying, and heat treatment; then, based on the graphene aerogel template, ceramic components such as boron nitride are deposited by chemical vapor deposition and crystallized; finally, the graphene component is removed by high-temperature oxidation treatment to obtain a ceramic aerogel with a negative Poisson's ratio and high elasticity. The ceramic aerogel obtained by the preparation method of the present invention exhibits excellent thermal insulation and fire resistance and good elasticity, and well solves the technical problems of volume shrinkage and strength reduction existing in the traditional ceramic aerogel preparation process.

[0019] The following is an exemplary description of the preparation method of the heat-insulating, fire-resistant and elastic ceramic aerogel provided by the present invention. The preparation method may include the following steps.

[0020] (1) Preparation of elastic graphene aerogel: The graphene dispersion is placed in a mold, and then directional freeze casting is performed, and then freeze drying is performed after the directional freeze casting is completed to obtain graphene oxide aerogel; then, thermal reduction treatment is performed to obtain the elastic graphene aerogel.

[0021] In some embodiments, the concentration of the graphene dispersion may be 2 to 14 mg / mL, preferably 4 to 12 mg / mL. If the graphene concentration is too low, a three-dimensional skeleton cannot be formed; if the concentration is too high, raw materials will be wasted.

[0022] In some embodiments, the mold may be a cylindrical hollow mold; the inner diameter of the cylindrical hollow mold may be 6 to 20 mm, the height may be 6 to 20 mm, and the mold wall thickness may be 0.5 to 2 mm.

[0023] In some embodiments, the directional freeze casting can be performed in liquid nitrogen, the ambient temperature can be -20 to -196°C, and the freeze casting time can be 1 to 20 minutes. Complete freezing means complete freezing, and the liquid nitrogen no longer boils, which means the freezing is over. If the freeze casting temperature is too low, it will not form a stable and continuous centripetal structure, and the negative Poisson's ratio effect will not be shown, and the mechanical properties will be poor. At the same time, if the freeze casting time is too low, it will not be completely frozen and a continuous structure cannot be formed. By controlling the appropriate freeze casting temperature and time range, it can be ensured that the graphene dispersion is completely frozen, and at the same time, a graphite oxide aerogel with a stable and continuous centripetal structure is obtained.

[0024] In some embodiments, the freeze-drying method can be vacuum freeze-drying, the drying temperature can be -40 to -20°C, preferably -40 to -30°C, the drying time can be 24 to 48 hours, and the vacuum degree can be 1 to 20Pa.

[0025] In some embodiments, the thermal reduction treatment may be carried out in an argon or nitrogen atmosphere, the thermal reduction temperature may be 800-1100°C, the heating rate may be 2-10°C / min, and the thermal reduction holding time may be 2-4h; preferably, the temperature is heated to 1000°C at a rate of 5°C / min in a nitrogen atmosphere and then held for 2h. A suitable thermal reduction system can better reduce graphene oxide to reduced graphene oxide and obtain high-quality graphene aerogel.

[0026] The present invention adopts a centripetal freeze casting method to obtain a graphene aerogel with a centripetal structure. The obtained aerogel has a negative Poisson's ratio effect and can be endowed with excellent elasticity and stability.

[0027] (2) Preparation of graphene / ceramic composite aerogel: Using the elastic graphene aerogel as a template, a ceramic component is in situ deposited on the surface of the elastic graphene aerogel by chemical vapor deposition, and after the deposition is completed, a heat treatment is performed to crystallize the ceramic component to obtain the graphene / ceramic composite aerogel.

[0028] In some embodiments, the ceramic component deposited by chemical vapor deposition may be boron nitride, silicon carbide, or silicon nitride ceramic, preferably boron nitride ceramic.

[0029] In some embodiments, the deposition temperature of the chemical vapor deposition ceramic component can be 500-1100° C., preferably 700-1100° C.; the deposition time can be 20-120 min, preferably 20-80 min. The thickness of the ceramic component can be controlled by controlling the deposition time.

[0030] Preferably, the precursors of the chemical vapor deposition ceramic component may include boron trichloride and ammonia, trichloroborazine, diethanolamine borate, and trichloromethylsilane. If the deposition time is too short, the deposit will not react and cannot be deposited on the template; if the deposition time is too long, the ceramic component will be transformed into a porous ceramic with high brittleness.

[0031] In some embodiments, the heat treatment temperature can be controlled to be 1300°C < ≤ 2400°C, preferably 2000°C; the heat treatment atmosphere can be argon or nitrogen atmosphere, preferably nitrogen atmosphere; and the heat treatment time can be 1 to 3 hours.

[0032] The ceramic components obtained by chemical vapor deposition at a lower temperature often show an amorphous phase, are easily oxidized, and have low strength. The present invention uses a crystallization treatment to improve its strength based on the negative Poisson's ratio effect obtained by centripetal freeze casting to achieve stability, thereby obtaining an oxidation-resistant, high-strength elastic ceramic aerogel. By controlling the appropriate crystallization heat treatment temperature and time, the crystallinity of the ceramic component can be guaranteed.

[0033] (3) Preparation of thermal insulation, fire-resistant and elastic ceramic aerogel. The graphene component of the above-mentioned graphene / ceramic composite aerogel is removed by thermal etching and oxidation to obtain the thermal insulation, fire-resistant and elastic ceramic aerogel.

[0034] In some embodiments, the thermal etching oxidation may be performed in an air atmosphere, the thermal etching temperature may be 600 to 800° C., preferably 700 to 750° C., and the time may be 20 to 40 minutes.

[0035] The preparation method provided by the present invention uses a sacrificial template method to obtain a negative Poisson's ratio ceramic aerogel with a customized three-dimensional concave structure; based on the sacrificed graphene aerogel structure, a ceramic component is deposited on the graphene surface by a chemical vapor deposition method to obtain a graphene / ceramic composite aerogel with the same structure; and then the graphene component is removed by thermal etching oxidation to obtain a ceramic aerogel after the sacrificial template, which has the same orientation structure as the graphene aerogel and exhibits a negative Poisson's ratio effect. The negative Poisson's ratio effect causes the aerogel to shrink laterally when compressed, and the internal stress mode is mainly compressive stress, which can inhibit crack propagation and is beneficial to improving the mechanical properties and stability of the ceramic aerogel. In addition, the chemical vapor deposition process replicates the template size and does not cause volume shrinkage problems. This metamaterial property of the negative Poisson's ratio effect can improve the elasticity and mechanical properties of porous materials and give the ceramic aerogel excellent elasticity.

[0036] The structural orientation of the ceramic aerogel provided by the present invention is derived from centripetal freeze casting. During the freeze casting process, a temperature gradient from the surface of the solution to the center of the solution is formed, that is, a centripetal temperature gradient. The growth direction of ice crystals is parallel to the temperature gradient. The ice crystals grow from the inner surface of the copper mold to the center under the influence of the centripetal temperature gradient. After the solution is completely frozen, the directional growth of the ice crystals is completed. The graphene oxide sheets in the dispersion are squeezed to the ice crystal interface during the growth of the ice crystals, and the interior of the aerogel obtained thereby forms a growth contour of centripetally oriented ice crystals, that is, a three-dimensional concave structure.

[0037] The present invention utilizes a directional freezing method with a centripetal temperature gradient to form a three-dimensional concave structure inside, and the structural network is composed of a double layer. Since the internal orientation of the ceramic aerogel replicates the three-dimensional concave structure of the graphene aerogel, it also has a negative Poisson's ratio effect. The resulting isotropic volume contraction and stress mode dominated by compressive stress enable the ceramic aerogel to maintain a stable structure and high elastic properties, and has excellent thermal insulation and fire resistance.

[0038] The density of the heat-insulating refractory elastic ceramic aerogel obtained by the preparation method provided by the present invention is 4 to 15 mg / cm 3 ; The mechanical properties were tested by a universal test, and 60% to 98% of the original height was retained after 1 to 100 compression cycles at a compression strain of 10 to 50%; and it was observed by a thermal infrared camera that it could stably exist under a 900°C flame. The thermal insulation, fire-resistant elastic ceramic aerogel has a low density, good thermal insulation and flame retardant effects, high mechanical strength and good resilience, and has great application value.

[0039] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0040] Example 1

[0041] The method for preparing the heat-insulating, fire-resistant and elastic ceramic aerogel provided in Example 1 of the present invention comprises the following steps: (1) adding graphene oxide to deionized water, and obtaining a uniformly dispersed graphene oxide dispersion with a concentration of 8 mg / mL after ultrasonic dispersion, pouring the uniformly dispersed graphene oxide dispersion into a cylindrical hollow copper mold until it overflows and then sealing it with copper, placing the sealed mold in liquid nitrogen and performing centripetal freeze casting at -196°C for 20 minutes, and after being completely frozen, vacuum drying the frozen sample at -20°C for 48 hours to obtain graphene oxide aerogel; then, placing the graphene oxide aerogel in a vacuum furnace, heating it to 1000°C at a rate of 5°C / min in an argon atmosphere, and then keeping it warm for 2 hours to obtain elastic graphene aerogel; (2) placing the elastic graphene aerogel in a tubular furnace to deposit a BN ceramic component at a deposition temperature of 1100° C. for 40 min; then, heat treating at 2000° C. for 3 h to crystallize the BN ceramic component to obtain a graphene / boron nitride ceramic composite aerogel; (3) The graphene / boron nitride ceramic composite aerogel after the above heat treatment is placed in a muffle furnace for heat treatment at 750° C. for 30 min to oxidize and remove the graphene component, thereby obtaining a heat-insulating, refractory, elastic boron nitride ceramic aerogel.

[0042] Figure 1 This is a scanning electron microscope image of the longitudinal section of the boron nitride aerogel prepared in Example 1; the left image shows the centripetal structural characteristics of the aerogel, and the right image shows the hollow double-layer structure of the lamellae. It can be seen from the figure that the structural orientation of the boron nitride aerogel prepared in Example 1 replicates the structural orientation of the graphene aerogel, presenting a unique "bouquet-shaped" orientation in the diagonal direction, and the boron nitride lamellae converge in the diagonal direction. In addition, a special "Y"-shaped structure formed at the end point of ice crystal convergence can be observed. This convergent structure is similar to the traditional two-dimensional concave structure, giving the boron nitride aerogel a negative Poisson's ratio effect, and the volume contraction in all directions causes the internal stress mode to be transformed into a compressive stress-dominated mode, thereby avoiding crack expansion and structural collapse.

[0043] Figure 2 The stress-strain curve of the boron nitride aerogel prepared in Example 1 after 100 compression cycles at a compression strain of 50%. It can be seen from the figure that the boron nitride aerogel prepared in Example 1 still retains 95% of its original height after 100 compression cycles at a compression strain of 50%.

[0044] Figure 3 This is a diagram of the negative Poisson's ratio effect of the boron nitride aerogel prepared in Example 1. As can be seen from the figure, the aerogel always exhibits a negative Poisson's ratio effect during the compression process, that is, lateral contraction occurs under longitudinal compression.

[0045] Figure 4This is a flame retardant and fire resistant performance diagram of the boron nitride aerogel prepared in Example 1. It can be seen from the figure that under the observation of an infrared camera, it can be exposed to a 900°C flame for more than 15 minutes, and the back of the aerogel still maintains a low temperature, indicating that it has excellent thermal insulation and fire resistance.

[0046] Example 2

[0047] The preparation method of this embodiment 2 refers to that of embodiment 1, with the main difference being that the time for chemical vapor deposition of BN in step (2) is 20 minutes.

[0048] Example 3

[0049] The preparation method of this embodiment 3 refers to that of embodiment 1, with the main difference being that the time for chemical vapor deposition of BN in step (2) is 30 minutes.

[0050] Example 4

[0051] The preparation method of this embodiment 4 refers to that of embodiment 1, with the main difference being that the time for chemical vapor deposition of BN in step (2) is 50 minutes.

[0052] Example 5

[0053] The preparation method of this Example 5 refers to that of Example 1, with the main difference being that the time for chemical vapor deposition of BN in step (2) is 60 minutes.

[0054] Example 6

[0055] The preparation method of this embodiment 6 refers to that of embodiment 1, with the main difference being that the thermal etching temperature in step (3) is 600°C.

[0056] Example 7

[0057] The preparation method of this embodiment 7 refers to that of embodiment 1, with the main difference being that the thermal etching temperature in step (3) is 700°C.

[0058] Comparative Example 1

[0059] The preparation method of this comparative example 1 refers to that of Example 1, with the main difference being that the heat treatment temperature in step (2) is 1300°C.

[0060] Figure 5 The stress-strain curve of the boron nitride aerogel prepared in Comparative Example 1 after 10 compression cycles at a compression strain of 50%. As can be seen from the figure, it exhibits lower compressive strength and elasticity.

[0061] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a heat-insulating, refractory, elastic ceramic aerogel, characterized in that: The preparation method comprises the following steps: (1) placing a graphene dispersion into a mold, and then performing directional freeze casting, and then freeze drying after the directional freeze casting to obtain graphene oxide aerogel; then, performing thermal reduction treatment to obtain elastic graphene aerogel; (2) using the elastic graphene aerogel as a template, in-situ depositing a ceramic component on the surface of the elastic graphene aerogel by a chemical vapor deposition process, and performing a heat treatment after the deposition is completed to crystallize the ceramic component to obtain a graphene / ceramic composite aerogel; (3) removing the graphene component from the graphene / ceramic composite aerogel by thermal etching and oxidation to obtain a heat-insulating, fire-resistant, elastic ceramic aerogel.

2. The preparation method according to claim 1, characterized in that: The concentration of the graphene dispersion is 2 to 14 mg / mL, preferably 4 to 12 mg / mL.

3. The preparation method according to claim 1 or 2, characterized in that: The mold is a cylindrical hollow mold; the inner diameter of the cylindrical hollow mold is 6-20 mm, the height is 6-20 mm, and the mold wall thickness is 0.5-2 mm.

4. The preparation method according to any one of claims 1 to 3, characterized in that The directional freezing casting is carried out in liquid nitrogen, the ambient temperature is -20 to -196°C, and the freezing casting time is 1 to 20 minutes.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The thermal reduction treatment adopts an argon atmosphere or a nitrogen atmosphere, the thermal reduction temperature is 800-1100°C, the heating rate is 2-10°C / min, and the thermal reduction holding time is 2-4h; preferably, heating to 1000°C at a rate of 5°C / min in a nitrogen atmosphere and then holding for 2h.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The ceramic component deposited by chemical vapor deposition is boron nitride, silicon carbide, silicon nitride ceramic, preferably boron nitride ceramic.

7. The preparation method according to any one of claims 1 to 6, characterized in that The deposition temperature of the chemical vapor deposition ceramic component is 500-1100° C., preferably 700-1100° C.; the deposition time is 20-120 min, preferably 20-80 min.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The heat treatment temperature is controlled to be 1300°C<heat treatment temperature≤2400°C, preferably 2000°C; the heat treatment atmosphere is argon or nitrogen atmosphere; and the heat treatment time is 1 to 3 hours.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The thermal etching oxidation is carried out in an air atmosphere, the thermal etching temperature is 600-800° C., preferably 700-750° C., and the time is 20-40 minutes.

10. A heat-insulating, refractory, elastic ceramic aerogel obtained by the preparation method according to any one of claims 1 to 9.